No time, no room: On‐shift teaching for any shift. Issue 4 (22nd December 2021) - Khamees, Deena; Wolff, Meg
Abstract: It can be difficult to carve out dedicated time to teach in the busy environment of the Emergency Department. With some intention, you can find educational opportunities in every shift. Here we highlight some of those opportunities, with careful attention to those without special equipment or preparation required. These can be used to teach less traditional practice points such as interprofessional communication as well as clinical pearls. Select the moments that make the most sense for you, your trainees, and your shift.